2013
DOI: 10.1093/carcin/bgt271
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of pathways involved in lung carcinoid progression using gene expression profiling

Abstract: Pulmonary carcinoids comprise a well-differentiated subset of neuroendocrine tumors usually associated with a favorable prognosis, but mechanisms underlying disease progression are poorly understood. In an explorative approach to identify pathways associated with progression, we compared gene expression profiles of tumors from five patients with a favorable and five with a poor disease outcome. Differentially expressed genes were validated using quantitative real-time PCR on 65 carcinoid tumors, in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 59 publications
3
45
0
1
Order By: Relevance
“…MiR-431-5p has never been associated with metastatic properties so far, while miR-409, with special reference to miR-409-3p, has been shown to inhibit cell migration and/or invasion in fibrosarcoma [17], bladder cancer [18] and gastric cancer [19] cells. Our findings shed light on molecular anomalies associated with lymph node dissemination of lung carcinoids and might prove to add clinically relevant prognostic information to the traditional mitotic count and presence of necrosis parameters [7,20,21]. In fact, predictive in silico analysis of genes targeted by the 3 microRNAs associated with metastatic disease revealed that all 3 microRNAs modulate similar cellular functions.…”
Section: Discussionmentioning
confidence: 77%
“…MiR-431-5p has never been associated with metastatic properties so far, while miR-409, with special reference to miR-409-3p, has been shown to inhibit cell migration and/or invasion in fibrosarcoma [17], bladder cancer [18] and gastric cancer [19] cells. Our findings shed light on molecular anomalies associated with lymph node dissemination of lung carcinoids and might prove to add clinically relevant prognostic information to the traditional mitotic count and presence of necrosis parameters [7,20,21]. In fact, predictive in silico analysis of genes targeted by the 3 microRNAs associated with metastatic disease revealed that all 3 microRNAs modulate similar cellular functions.…”
Section: Discussionmentioning
confidence: 77%
“…This methodological study paves the way to the use of Ki-67 LI in a daily diagnostic setting to characterize metastatic lung NET [21,33,38]. On surgical specimens of lung NET, some methodological studies on quantification of Ki-67 staining to generate a Ki-67 LI by manual or automated analysis systems have been performed [17,19,32,[39][40][41]. None, however, compared biopsies with corresponding surgical specimens, probably because in these tumors, the Ki-67 LI is not used for diagnosis or grading or as a prognostic factor [4,6,30], as morphology remains the favored approach [3].…”
Section: Discussionmentioning
confidence: 99%
“…In metastatic lung NET, the importance of the Ki-67 LI on biopsy samples is not so much the diagnosis as such (which paradoxically matters less once high-grade NET has been excluded) but rather to guide subsequent therapy choice [33]. This molecular, morphological, and clinical heterogeneity of lung NET [20,39,[46][47][48][49][50] is similar to that of G3 GEP NET for which the Ki-67 LI is of equal diagnostic importance [26,[51][52][53][54][55][56]. Of note, LCNECs of the lung show a wide range of histological and molecular features, as some cases are morphologically close to SCCs [13, 14,16,47], while others are closer to conventional non-small cell carcinoma [47,[57][58][59]] and yet others to AC [3,8,47].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found no association between Bub1 mRNA and protein levels and chemoresponse or survival. However, Bub1 expression has been associated with aggressive clinical behavior in other cancers, including breast carcinoma, endometrial carcinoma, malignant melanoma, and pulmonary carcinoid [28][29][30][31][32]. Whether Bub1 may have such role in early-stage serous OC or in other histological subtypes of OC remains to be determined.…”
Section: Discussionmentioning
confidence: 99%